The rhetorical design of Isaiah 40-48/55 Zion's incomparable saviour and his servants - Lugt, Pieter van der (Leiden Boston Brill, 2022)
"In this volume, Pieter van der Lugt offers a comprehensive analysis of the rhetorical structure of Isaiah. As in his previous studies on the Book of Job and the Psalter the author demonstrates that classical Hebrew poetry displays a well-defined structure consisting of balanced main parts (cantos) and subdivision into strophes. This rhetorical starting point is of crucial importance for the delimitation of the individual poems in Isaiah 40-48 and in many cases determines their interpretation. Subsequently, it is demonstrated that the successive compositions form well-defined and coherent cycles of poems"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Socio-rhetorical criticism